The Diamond Model of Open Access Publishing: Why Policy Makers, Scholars, Universities, Libraries, Labour Unions and the Publishing World Need to Take Non-Commercial, Non-Profit Open Access Serious - Christian Fuchs; Marisol Sandoval (tripleC: Communication, Capitalism & Critique, 2013)
This reflection introduces a new term to the debate on open access publishing: diamond open access (DOA) publishing. The debate on open access is a debate about the future of academia. We discuss the problems of for-profit academic publishing, such as monopoly prices and access inequalities and point at the limits of contemporary perspectives on open access as they are frequently advanced by the publishing industry, policy makers and labour unions. The article introduces a public service and commons perspective that stresses the importance of fostering and publicly supporting what we term the model of diamond open access. It is a non-profit academic publishing model that makes academic knowledge a common good, reclaims the common character of the academic system and entails the possibility for fostering job security by creating public service publishing jobs. Existing concepts such as “gold open access” have serious conceptual limits that can be overcome by introducing the new term of diamond open access. The debate on open access lacks visions and requires social innovations. This article is a policy intervention and reflection on current issues related to open access (OA) publishing. It reflects on the following questions: * What should the role of open access be in the future of academic publishing and academia? * How should the future of academic publishing and academia look like? * Which reforms of academic policy making are needed in relation to open access publishing? We want to trigger a new level of the open access debate. We invite further reflections on these questions by academics, policy makers, publishers, publishing workers, labour unions, open access publishing associations, editors and librarians. Twitter: #DiamondOA